2018
DOI: 10.1007/978-3-319-94580-4_20
|View full text |Cite
|
Sign up to set email alerts
|

A Network-Oriented Adaptive Agent Model for Learning Regulation of a Highly Sensitive Person’s Response

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal ? Take down policyIf you believe that this document breaches c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The first point refers to SPS having a negative effect on well-being, self-control, and sociability as well as on increasing the potential for avoidant and spontaneous decision-making. Considering the increased benefits highly sensitive persons receive from positive interventions [ 2 ], one relevant way may be through a supportive person with average sensitivity (acting as external regulating agent) to regulate distress and reduce the overwhelming stimuli, thereby aiding the highly sensitive person to cope with disconcerting stimuli [ 47 ]. The second point refers to the importance of emotional reactivity and specifically negatively impacted well-being in highly sensitive persons.…”
Section: Discussionmentioning
confidence: 99%
“…The first point refers to SPS having a negative effect on well-being, self-control, and sociability as well as on increasing the potential for avoidant and spontaneous decision-making. Considering the increased benefits highly sensitive persons receive from positive interventions [ 2 ], one relevant way may be through a supportive person with average sensitivity (acting as external regulating agent) to regulate distress and reduce the overwhelming stimuli, thereby aiding the highly sensitive person to cope with disconcerting stimuli [ 47 ]. The second point refers to the importance of emotional reactivity and specifically negatively impacted well-being in highly sensitive persons.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study of highly sensitive individuals also found that they considered positivity, acceptance, and reflection as helpful psychological strategies for coping with negative thoughts (Bas et al., 2021 ). Also, a recent study that used a computational‐based approach indicated that highly sensitive individuals internalise emotional regulation strategies modelled by another (not highly sensitive) person (Tran, Treur, & Tuinhof, 2018 ). The results highlight the potential benefit of therapists practising implementing emotion regulation strategies with highly sensitive young people within the therapy sessions , as opposed to relying solely on the young practising them in between sessions.…”
Section: Differential Susceptibility Theory and Its Potential Impact ...mentioning
confidence: 99%